Family Planning and Mother’s Practice In Children’s Feeding In Bengkulu Province, Indonesia - Simbolon, Demsa; Bathari, Rosalia Rina; Rahmadewi, Rahmadewi; Riastuti, Frensi (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Family planning will affect the mother’s ability in parenting which will affect the children’s growth and development. This study aims to determine the relationship between family planning and the practice of child feeding (PCF). The study used Indonesian Demographic and Health Survey 2017 data with a cross-sectional approach. Family planning is measured by variables age at first marriage, the distance between births, parity, number of children under five, and pregnancy desired. The PCF is based on the variable composite of Early Initiation of Breastfeeding, Exclusive Breastfeeding, Infant and Child Feeding, and Consumption of food sources of vitamin A. The sample size is 97 children aged 6-23 months. Data analysis using multivariate logistic regression. The study results that almost part of the mother did not PCF well (45.4%). Most (69.1%) mothers were not good at family planning. Family planning related to poor PCF was age at first marriage less than 18 years (p = 0.003) primiparous parity (p = 0.017), 2-5 years birth spacing (p = 0.033) and the number of children under five (p = 0.025). There need to be more educational efforts, outreach and family planning movements so that people, especially teenagers, understand the importance of family planning.